Curing Methods for Advanced Polymer Composites - A Review. Issue 6 (July 2013) - Abliz, Dilmurat; Duan, Yugang; Steuernagel, Leif; Xie, Lei; Li, Dichen; Ziegmann, Gerhard
Advanced polymer composites have obtained great application interest in a number of demanding aerospace, wind energy, automotive, infrastructure, and consumer applications. Great varieties of curing methods are investigated to develop low-cost and high-efficient fabrication of advanced polymer composites, which still remains as a great challenge and thorny issue. Especially, the autoclave curing process, which is widely used for curing of high performance advanced polymer composites, is labor- and capital-intensive, with costs increasing exponentially with part size and limiting increased use of advanced polymer composites. Researchers and industries have long desired to explore and develop low-cost and high-efficient curing methods for fabrication of advanced polymer composites and investigated different radiation and thermal curing alternatives. In this paper, current development status of the radiation curing (gamma ray, x-ray, ultraviolet, accelerated electron beams) and thermal curing (radiation heating (infrared, laser and microwave), convection and conduction heating (hot gas, flame, oven and hot shoe), induction heating, ultrasonic heating, resistance heating and thermal additives (magnetic particles, NIR absorbent particles) based heating methods applied for the curing of advanced polymer composites are reviewed. The curing mechanism and current application status of the different curing processes for fabrication of advanced polymer composites is discussed, and main advantages and disadvantages of these methods are comparatively analysed and evaluated according to the material, cost, feasibility and power criteria for successful curing application of advanced polymer composites.